2007
DOI: 10.1002/jssc.200700316
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new C14 monolithic silica column containing embedded polar groups for pressurized capillary electrochromatography

Abstract: Monolithic columns have been prepared with a novel bonded silica stationary phase, tetradecylamine bonded silica (TDAS), and used in pressurized capillary electrochromatography (pCEC). The monolithic silica column matrix was prepared by a sol-gel process and then chemically modified with the spacer (3-glycidoxypropyl)trimethoxysilane and tetradecylamine. The introduced embedded polar amine groups dominated the charge on the surface of the monolithic stationary phase and generated an EOF from cathode to anode u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…A phase containing both ether and amino embedded groups (and a hydroxyl group) has been used in CEC (Ye, Li, and Zhao 2007). This gave improved peak symmetry for anilines as the positively charged amino-embedded group prevented adsorption of analyte onto the surface.…”
Section: Ether Embedded Phasesmentioning
confidence: 99%
“…A phase containing both ether and amino embedded groups (and a hydroxyl group) has been used in CEC (Ye, Li, and Zhao 2007). This gave improved peak symmetry for anilines as the positively charged amino-embedded group prevented adsorption of analyte onto the surface.…”
Section: Ether Embedded Phasesmentioning
confidence: 99%
“…pH values greatly influence separation, based on the results from the experiments (9,19,20), the resolution was lower when this value was above or below 4.5. This was attributed to the characteristics of the monolith and the target compound.…”
Section: Influences Of Each Factors On Separationmentioning
confidence: 92%
“…The combination of the two offers a promising alternative. It was shown that a hybrid organic–inorganic monolithic column incorporates the organic functional moieties into the inorganic silica monolith by the sol–gel process, which yields various properties . Compared with the conventional procedure that involves forming a silica matrix and subsequent chemical bonding, direct incorporation of organosiloxanes was more preferable attributed to its better hydrolytic stability at low pH values.…”
Section: Introductionmentioning
confidence: 99%
“…The GNPs were synthesized based on the sodium citrate synthesis method as reported previously 24. The bare monolithic silica capillary column was prepared according to the procedures described in the previous literature 30. A solution of 10% v/v MPTMS in toluene was passed through the activated bare monolithic silica capillary column and made to react at 110°C in the drying oven for 1 h; this step was repeated four times.…”
Section: Methodsmentioning
confidence: 99%